The Effect Of Peanut Extract As A Cow’s Milk Substitute On The Physical And Sensory Quality Of Diplomat Cream - Nadia Salma Maharani; Mutiara Dahlia; Efrina Efrina (Community Engagement and Emergence Journal (CEEJ), 2026)
The increasing demand for plant-based food products has encouraged the development of alternatives to cow's milk in pastry products. This study aimed to analyze the effect of different peanut-to-water ratios in peanut extract on the physical quality and sensory attributes of diplomat cream. An experimental method was applied using three treatment ratios of peanut to water: 1:1, 1:1.5, and 1:2. Physical quality was evaluated through pH and volume consistency tests using ANOVA, while sensory quality was assessed using the Kruskal-Wallis test with 45 semi-trained panelists. Results indicated that peanut extract ratio significantly affected the pH value of diplomat cream (F-count 31.63 > F-table 5.143), with mean pH values of 5.41, 5.39, and 5.28 for the 1:1, 1:1.5, and 1:2 treatments, respectively. Duncan's test showed that the 1:2 treatment differed significantly from the other two treatments. Volume consistency was not significantly affected (F-count 0.29 < F-table 5.143). Sensory evaluation revealed no significant differences in color, consistency, texture, and sweetness among treatments, but significant differences were found in peanut aroma (H-count 7.17 > χ²-table 5.991) and peanut flavor (H-count 13.17 > χ²-table 5.991). The 1:2 treatment produced the most neutral sensory characteristics, closest to the control diplomat cream. Therefore, peanut extract at a 1:2 ratio is recommended as the best formulation to substitute cow's milk in diplomat cream production.